DETERMINATION OF THE TRANSFER CAPABILITY OF THE TUNED POWER TRANSMISSION OF ITAT-CHELYABINSK WHILE AVAILABLE IN ITS COMPLETION OVERHEAD LINE ITAT-EKIBASTUS-CHELYABINSK (IN THE 1150 KV DIMENSIONS) - Anton Potapenko; Tatyana Krasilnikova (Вестник Северо-Кавказского федерального университета, 2022)
This article justifies the transfer capability of the tuned power transmission of Itat-Chelyabinsk power transmission line, which includes the Itat-Ekibastuz-Chelyabinsk line in the 1150 kV dimensions, which is currently operating at a voltage of500 kV. The stages of operation of tuned power transmission at a voltage of 500 kV and 750 kV are considered taking into account all technical limitations. The analysis made it possible to estimate the transfer capability of the Itat-Ekibastuz-Chelyabinsk overhead transmission line as part of the tuned Itat-Chelyabinsk power transmission line (TPT), and to make a conclusion about the necessity of developing special equipment for the implementation of TPT circuit variants at a voltage of500 kV and 750 kV. The technical requirements for the development of tuning reactors for TPT operation at full transfer capability are defined.